Quantifying the Role of Lysine in Prion Replication by Nano-LC Mass Spectrometry and Bioassay - Silva, Christopher J.; Erickson-Beltran, Melissa L.; Dynin, Irina C. (Frontiers in Bioengineering and Biotechnology, 2020)
Prions propagate by a template driven process, inducing the normal cellular isoform (PrPC) to adopt the prion (PrPSc) conformation. In PrPC, the positions of lysines are highly conserved and strongly influence prion propagation. In this study, covalent modification was used to quantitate the role of lysines in the PrPSc template that drives prion replication. The -amino group of lysines in the PrPSc (hamster-adapted scrapie Sc237) template was acetylated by either acetic anhydride (Ac2O) or the N-hydroxysuccinimide ester of acetic acid (Ac-NHS). The extent of lysine acetylation in PrPSc was quantitated by mass spectrometry or Western blot-based analysis. Identical samples were bioassayed to quantitate the loss of infectivity associated with lysine acetylation. The reduction of infectivity at the highest reagent concentration was approximately 90% (~10-fold). Ten of the eleven prion lysines were acetylated to a greater extent (25-400-fold) than the observed loss of infectivity. Only one lysine, at position 220 (K220), had a reactivity that correlated with the loss of infectivity. Although lysines are highly conserved and play a crucial role in converting PrPC into the PrPSc conformation, once that conformation is adopted, the lysines present in the PrPSc template play only a limited role in prion replication. In principle, this approach can be used to clarify the role of other amino acids in prion replication. It can also be used to clarify the role that lysines play in the propagation of other prion-like protein misfolding diseases such as Alzheimer’s Disease, Amyotrophic Lateral Sclerosis, and Parkinson’s Disease.